Improving Student Learning Outcomes on Earth Layers Material by Using Audio Visual Media - Fatonah, Annisa; Worku, Hassen; Inyang, Francis (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The researcher aims to determine the increase in student learning outcomes in the earth's layers material by using audio-visual media. Methodology: This research is classroom action research. The subjects in this research were 7th grade students with a total of 39 students using a simple random sampling technique. The data collection instruments in this research consisted of multiple choice questions, observation sheets for teachers and students and documentation. Data analysis uses descriptive statistical analysis. Main Findings: The results of this research found that by using audio visual media students were more enthusiastic in participating in learning and with the help of discussion methods students were more active and discussing with groups, with audio visual media students' learning outcomes also increased, from the learning of each cycle in class VII F students a number There were 39 students who had not achieved learning completeness, 20 students in cycle I and 2 students in cycle II. After implementing the learning actions, there were still 2 students whose scores were less than 75 or had not reached the minimum completeness criteria of 75. Then these students were given further study guidance and given remedial measures. Novelty/Originality of this study: The novelty of this research is that it shows adaptation to students' learning styles or individual needs in the context of earth layer material, this can be considered an innovative step. A personalized learning approach can increase learning effectiveness.